Poetic Language and Gender: Interpreting Abba’s Song Lyrics to Uncover the Portrayal of Women Stereotype - Mairanata, Heronimus Rama Theola Putra; Trihastutie, Nopita; Rusnalasari, Zulidyana Dwi (TEKNOSASTIK, 2024)
The songs Angeleyes (1979), Lay All Your Love on Me (1980), and Slipping Through My Fingers (1981) by ABBA are examined in this research. This study looks at how women are stereotypically portrayed in ABBA songs. This study examines how gender is portrayed in roles, particularly as it relates to women, using Linda Brannon's Gender Stereotype theory. Information is derived from many texts and the song's lyrics. The research's content is explained using a qualitative descriptive technique. The research's conclusions are based on the usage of the topic and style of the language of love, which employs metaphors in figurative language. It is from metaphorical language that the notion of love arises, symbolizing the characteristics of the feminine gender. The conversation that followed clarified that song lyrics are a form of poetry writing and that specific metaphorical language also has significance in how women are portrayed. According to the study, a song's content and lyrical style create stereotypes of women, creating a metaphorical figurative language. This use of metaphorical language gives the song's lyrics a meaning related to love. The song lyrics illustrate the virtues and faults of women by defining love in several ways. These items are all related to one another.